LEGAL ASPECTS OF EUROPEAN UNION ARMAMENTS COOPERATION: CHALLENGES AND OPPORTUNIES FOR INTEGRATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
European armaments cooperation is governed by a complex legal framework, integrating international agreements, EU regulations, and national laws. Given the evolving geopolitical situation in Europe, marked by active and frozen conflicts near EU borders, the need for efficient and transparent legal mechanisms in defense cooperation has become more urgent. The paper explores the legal aspects of cooperative armament programs, assessing key regulatory challenges and institutional mechanisms, such as the European Defence Fund, Permanent Structured Cooperation, and the European Defence Agency. It examines the interplay between EU law and national sovereignty, focusing on Article 346 Treaty on the Functioning of the European Union and its implications for defense procurement and competition rules. By identifying legal uncertainties and proposing solutions to enhance transparency and effectiveness, the study highlights the necessity of legal harmonization to strengthen Europe’s strategic autonomy and security resilience in the current geopolitical climate.